Pengaruh Kompetensi Sosial Guru Terhadap Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Islam - Fauziah, Hapsah; Daerobi, Enceng Muhamad (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
The success of the learning process in the classroom can be seen from students' interest in learning. Because students' interest in learning will achieve maximum results if teachers who are directly involved in the learning process have social competence, mastery of material broadly and deeply will not be conveyed properly to students if the teacher is unable to communicate actively with students. Teacher's social competence is the ability to communicate and interact actively and efficiently with students, other teachers, employees, parents, principals and the surrounding community.The purpose of this study is to describe; the influence of teacher's social competence on students' interest in learning Islamic religious education subjects. Thus, it can find out the extent of the influence of teacher social competence (Variable X) on student interest in learning (Variable Y). The method used in this study, is an inferential quantitative method, by collecting data or information about the phenomenon under study. Data collection techniques by means of observation, interviews, questionnaires or questionnaires distributed to 57 respondents. While for data processing is done by statistical data analysis. The results showed that students' interest in learning in Islamic Religious Education subjects had an average of 26.59, thus the average value was in the interval area 2.01-3.00, including in a fairly good category. While the teacher's social competence has an average of 26.80, thus the average is in the interval area of 2.01-3.00, including in a fairly good category. Based on statistical tests, there is an effect of teacher social competence on student interest in Islamic religious education subjects by 32% which is categorized as good, while other factors that influence student learning outcomes as much as 68% students but are not examined in this study. Keywords: Teacher Social Competence, Student Learning Interest, PAI Subjects.